Does the human X contain a third evolutionary block? Origin of genes on human Xp11 and Xq28 - Delbridge, Margaret L.; Patel, Hardip R.; Waters, Paul D.; McMillan, Daniel A.; Marshall Graves, Jennifer A. (Genome Research, 2009)
Comparative gene mapping of human X-borne genes in marsupials defined an ancient conserved region and a recently added region of the eutherian X, and the separate evolutionary origins of these regions was confirmed by their locations on chicken chromosomes 4p and 1q, respectively. However, two groups of genes, from the pericentric region of the short arm of the human X (at Xp11) and a large group of genes from human Xq28, were thought to be part of a third evolutionary block, being located in a single region in fish, but mapping to chicken chromosomes other than 4p and 1q. We tested this hypothesis by comparative mapping of genes in these regions. Our gene mapping results show that human Xp11 genes are located on the marsupial X chromosome and platypus chromosome 6, indicating that the Xp11 region was part of original therian X chromosome. We investigated the evolutionary origin of genes from human Xp11 and Xq28, finding that chicken paralogs of human Xp11 and Xq28 genes had been misidentified as orthologs, and their true orthologs are represented in the chicken EST database, but not in the current chicken genome assembly. This completely undermines the evidence supporting a separate evolutionary origin for this region of the human X chromosome, and we conclude, instead, that it was part of the ancient autosome, which became the conserved region of the therian X chromosome 166 million years ago.
10.1101/gr.088625.108